Differences in Child Care Quality in Rural and Non-Rural Areas - Erin J. Maher; Becki Frestedt; Cathy Grace (Journal of Research in Rural Education, 2008)
This study examines rural differences in one important indicator of quality for licensed child care settings"the number of children per adult. It also investigates the relationships between cost of child care, child care subsidy receipt, and child care quality for both rural and non-rural areas. We used representative child care survey data pooled across five states with geographic identification of rural status at the zip code level. While controlling for other characteristics that may affect child:adult ratios, we found infants in center care in rural areas are more likely to experience higher child:adult ratios and preschoolers in center care in rural areas are more likely to experience lower child:adult ratios than their non-rural counterparts. Toddlers in family child care are more likely to experience lower child:adult ratios in rural than urban areas. In rural areas, the cost of family child care and center care, for the toddler age group only, is significantly associated with lower ratios. Infants and preschoolers whose families receive public child care subsidies are more likely to experience higher child:adult ratios regardless of whether they reside in a rural area or not. These results address the gap in knowledge about differences in child care quality in rural and non-rural areas and demonstrate that the relationship between one indicator of quality and rural status varies by age of children and type of care. However, children receiving child care subsidies are most consistently at risk for receiving lower quality care. Policies need to be in place to ensure low-income children receiving child care subsidies in both rural and non-rural areas have equal access to higher quality licensed care.